1997
DOI: 10.1074/jbc.272.33.20655
|View full text |Cite
|
Sign up to set email alerts
|

Presenilins Are Processed by Caspase-type Proteases

Abstract: Presenilin 1 (PS1) and presenilin 2 (PS2) are endoproteolytically processed in vivo and in cell transfectants to yield 27-35-kDa N-terminal and 15-24-kDa C-terminal fragments. We have studied the cleavage of PS1 and PS2 in transiently and stably transfected hamster kidney and mouse and human neuroblastoma cells by immunoblot and pulse-chase experiments. C-terminal fragments were isolated by affinity chromatography and SDS-polyacrylamide gel electrophoresis and sequenced. Mutant presenilin 1 and 2 (PS1, PS2)1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
100
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 28 publications
12
100
2
Order By: Relevance
“…Cytoplasmic cytochrome c participates in the activation of caspases (Kluck et al, 1997b;Li et al, 1997), a family of related cysteine proteases which cleave after aspartic acid residues (Salvesen and Dixit, 1997). Caspase activation is a universal and necessary feature of apoptosis, leading to the cleavage of enzymes regulating cell morphology, RNA processing, and DNA replication (Wen et al, 1997;Kothakota et al, 1997;Loetscher et al, 1997;Gu et al, 1995). Mitochondria also contribute to apoptosis through the apoptosis-induced release of an uncharacterized 50 kDa protease AIF (AIF: apoptosis inducing factor) into the cytoplasm .…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic cytochrome c participates in the activation of caspases (Kluck et al, 1997b;Li et al, 1997), a family of related cysteine proteases which cleave after aspartic acid residues (Salvesen and Dixit, 1997). Caspase activation is a universal and necessary feature of apoptosis, leading to the cleavage of enzymes regulating cell morphology, RNA processing, and DNA replication (Wen et al, 1997;Kothakota et al, 1997;Loetscher et al, 1997;Gu et al, 1995). Mitochondria also contribute to apoptosis through the apoptosis-induced release of an uncharacterized 50 kDa protease AIF (AIF: apoptosis inducing factor) into the cytoplasm .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to processing by the presenilinase, both PS proteins are substrates for proteinases of the caspase superfamily (31)(32)(33)(34). In this pathway the 20-kDa CTF 20 serves as a substrate for caspase cleavage (33) which generates a smaller ϳ10-kDa C-terminal fragment (Fig.…”
mentioning
confidence: 99%
“…The endoproteolytical cleavage of PS1 and PS2 yields 27−35 kDa N-terminal fragments (NTFs) and 15−24 kDa C-terminal fragments (CTFs). This cleavage of PS1 or PS2 can be prevented by blockade of caspase 1 or 3 activity or the mutation of caspase cleave sites, such as Asp 345 /Ser 346 for PS1 and Asp 329 / Ser 330 for PS2 [129]. It has been demonstrated that multiple caspases possess the ability to cleave presenilins.…”
Section: Multiple Pathways For Caspase Activity To Influence the Toximentioning
confidence: 99%